2012
DOI: 10.1007/s00330-012-2592-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of grating-based X-ray phase-contrast CT for differentiation of invasive ductal carcinoma and ductal carcinoma in situ in an experimental ex vivo set-up

Abstract: Our results indicate that unlike conventional CT, grating-based PC-CT may allow the differentiation between invasive carcinoma and intraductal carcinoma and healthy breast tissue and provide 3D visualisation of DCIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 24 publications
0
29
0
2
Order By: Relevance
“…Thus, PCI can clearly define weakly X-ray-absorptive biological soft tissues without the use of a contrast agent. Several PCI modalities have been developed, such as interferometry [10], diffraction enhanced imaging (DEI) [11, 12], grating-based phase-contrast X-ray imaging (GB-PCI) [13], and in-line phase contrast imaging (IL-PCI) [14, 15]. Among them, IL-PCI has no requirements of superior temporal coherence within the X-ray source and complex experimental apparatus in the light path.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PCI can clearly define weakly X-ray-absorptive biological soft tissues without the use of a contrast agent. Several PCI modalities have been developed, such as interferometry [10], diffraction enhanced imaging (DEI) [11, 12], grating-based phase-contrast X-ray imaging (GB-PCI) [13], and in-line phase contrast imaging (IL-PCI) [14, 15]. Among them, IL-PCI has no requirements of superior temporal coherence within the X-ray source and complex experimental apparatus in the light path.…”
Section: Introductionmentioning
confidence: 99%
“…First trials on ex vivo phase-contrast CT (PC-CT) imaging of breast samples showed greatly improved soft-tissue contrast and differentiability of fine structures compared to absorption-based imaging [15][17]. Microscopic structures like the walls of dilated ducts containing ductal carcinoma in situ can be visualized in PC-CT but not in absorption CT, an information that might be used for future differentiation between invasive and noninvasive carcinoma [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has great potential e.g. in medical diagnostics for the detection of breast cancer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%